The HIV Prison Paradox: Agency and HIV-Positive Women's Experiences in Jail and Prison in Alabama. (August 2017) - Sprague, Courtenay; Scanlon, Michael L.; Radhakrishnan, Bharathi; Pantalone, David W.
Incarcerated women face significant barriers to achieve continuous HIV care. We employed a descriptive, exploratory design using qualitative methods and the theoretical construct of agency to investigate participants' self-reported experiences accessing HIV services in jail, in prison, and post-release in two Alabama cities. During January 2014, we conducted in-depth interviews with 25 formerly incarcerated HIV-positive women. Two researchers completed independent coding, producing preliminary codes from transcripts using content analysis. Themes were developed iteratively, verified, and refined. They encompassed (a) special rules for HIV-positive women: isolation, segregation, insults, food rationing, and forced disclosure; (b) absence of counseling following initial HIV diagnosis; and (c) HIV treatment impediments: delays, interruption, and denial. Participants deployed agentic strategies of accommodation, resistance, and care-seeking to navigate the social world of prison and HIV services. Findings illuminate the "HIV prison paradox": the chief opportunities that remain unexploited to engage and re-engage justice-involved women in the HIV care continuum.